Violencia intrafamiliar y su influencia en las complicaciones del embarazo en adolescentes atendidas en el Centro de Salud Morales, distrito de Morales. Mayo - Octubre 2013 - Valderrama Araujo, Bania Karen (2013)
The present research aimed to determine the influence of domestic violence on adolescent pregnancy complications treated at the Health Center Morales, Morales District. May to October 2013. We performed a quantitative, correlational descriptive, transactional, with prospective data collection, non-probability sampling consists of 47 adolescents who suffered domestic violence, selected through a self-diagnostic questionnaire. The information obtained was poured into a database Excel 2012, then incorporated into the statistical package SPSS version 17.0, after coding. The analysis was performed by describing and comparing the type of domestic violence and the medical diagnosis of pregnant adolescents, in the descriptive analysis was used measures of central tendency and dispersion. In order to analyze the association of the variables involved in the study, we applied the bivariate correlation analysis "r " of Pearson. With the findings were arrived at the following conclusions: There is a positive significant relationship between Domestic Violence and Teen Pregnancy Complications. In order of precedence , 76.6 % of pregnant teenagers had urinary tract infections ; hyperemesis gravidarum 51.1 % , 42.6 % suffer from anemia , and 31.9 % had threatened abortion, 17% genital infections ; 14.9 IUGR , 8.5 % preterm labor , and gestational hypertension 6.4% . The 61.7 % develops an abusive family relationship, the 25.5 % takes place in the first level of abuse, 10.6% takes place in a family relationship of severe abuse, and 2.1% in the level of dangerous abuse . Psychological violence prevails with an average score of 4.83, followed by physical violence with an average score of 2.94; economic violence with an average of 2.79, and sexual violence is less prevalent with an average score of 1.62. The 95.7 % of pregnant teenagers are late teens, 61.7 %, are living together, and 38.3 % were single, and 63.8 % are housewives. Concluding: There is a positive significant relationship between Domestic Violence and Teen Pregnancy Complications